Establishment of humanized tumor microenvironment mouse models based on the injection of peripheral blood mononuclear cells and IFN-γ to evaluate the efficacy of PD-L1/PD-1-targeted immunotherapy. Issue 2 (1st February 2020) - Lin, Xiuyun; Zeng, Tao; Lin, Jinxiang; Zhang, Qiong; Cheng, Haoling; Fang, Shubin; Lin, Shuchun; Chen, Yuanzhong; Xu, Yunlu; Lin, Jizhen
ABSTRACT: Programmed death ligand-1 (PD-L1) expression and the presence of tumor-infiltrating lymphocytes (TILs) in tumor microenvironment were common in chronic inflammatory tumor types and frequently responded to the PD-L1 pathway immune checkpoint blockade in the clinic. Animal models to optimize such immunotherapeutics comprise an important strategy but often fail to predict the efficacy of clinical approaches. To address this, we aimed to establish new mouse models. In this study, we found that the expression of PD-L1was present at the beginning stage but a gradual decline over time in the in vitro cell culture and also in the mouse model. Based upon this finding, we established the IFN-γ-(human peripheral blood mononuclear cell) PBMC-CDX (cell line-derived xenograft) and IFN-γ-PBMC-PDX (patient-derived xenograft) mouse models, which recapitulate human tumor and human immune system interactions. IFN-γ was injected peritumorally to maintain the positivity of PD-L1 in the tumor microenvironment. Under this circumstance, the PD-1 molecule on the human T lymphocyte surface is in contact with the PD-L1 molecule on the human tumor cells and, thus, the formatin of the PD-L1/PD-1 pathway in the tumor microenvironment.Treatment with anti-PD-1 monoclonal antibody (mAb) significantly inhibited the growth of both CDX and PDX tumors, but not non-human NCG models (without allogeneic human PBMCs and IFN-γ) . These experimental data provide an important and promising platform for the development of drugs and the evaluation of the drug efficacy of immunotherapies with anti-PD-1 mAb as well as the basis of preclinical mAb drug research.